A Novel approach to measure the total antioxidant power of wines through near infrared spectroscopy and its relevance in human nutrition - Pastor, Raul Francisco (2019)
Abstract: Wine is the product of the alcoholic fermentation of the grape (Vitis vinifera). As such, it is a hydroalcoholic solution with a variable content of nutritional and functional (polyphenols) molecules, the latter involved in its antioxidant potential. The organoleptic variables of wine, together with its potential positive effects on health of a light-moderate intake, have always been topics of great interest within the cultures. In the label of wine, alcohol is the only declared variable. On the other hand, there is no information about the content of ?positive? molecules, such as those associated with the antioxidant power. This value could be very important to classify the wines, helping oenologist and nutritionist in qualifying them as a component of Mediterranean diet. Moreover, one of the most critical aspects in evaluating the role of wine in human health through epidemiological prospective studies is the quality of the products used and their antioxidant potential. This research aimed to optimize and validate an analytical approach based on a portable device (SCIO®), using NIRS (near-infrared reflectance spectroscopy). It allows the measure of TAP (total antioxidant power) of wine through the glass. Research findings are promising. To the best of our knowledge, this is the first time that an easy-to-use and cheap hand-held scanner is validated to measure the TAP of a beverage.